Strategi Pemasaran Usaha Kecil Dengan Memanfaatkan Media Sosial Sebagai Upaya Pengembangan Usaha Minuman Es Cokelat Aa’ Sawah Lebar Kota Bengkulu - Nurjaman, Ari; Indriasari, Nia (Universitas Dehasen Bengkulu, 2023)
Marketing strategy is one of the most important things in the business world as steps to achieve a predetermined goal. Marketing strategy as the main weapon to overcome all existing and future risks, especially for small businesses, of course, the risks that will be faced are more, such as competition with bigger entrepreneurs and with the same product, this is where the importance of strategy marketing as a business development effort, especially in small businesses. The purpose of this community service is to provide an understanding of the utilization of the existence of social media in this digital era as a means to introduce and promote AA' chocolate ice drink products widely in the city of Bengkulu. That the use of social media as a marketing strategy in this digital era is very effective in expanding the market network and making it easier for consumers to get information about the product they want by interacting through social media. The methodology used in this community service program is to provide an understanding of the benefits and importance of social media and assistance in creating social media accounts for media marketing strategies. There are 3 social media used, namely Instagram, Tik Tok, and Facebook.